Corona virus Covid 19: The Journey around the Globe so Far - Kavitha Chandu, Madhavaprasad Dasari (International Journal of Advanced Science and Technology, 2020)
Originating in China towards the end of 2019 Covid 19 spread across the Globe like wild fire terrorising over 190 countries. It starts with common cold leading to respiratory problems and death. The virus grows exponentially. The evidence shows that death rate peaked towards the end of February in China and Iran and its growth is even more alarming in European countries and USA by the third week of March 2020. The rate of spread appears to have slowed in countries like India due to preventive care or reduced human flows from countries with incidence of the virus to other countries. Extensive social distancing appears to address slowing down of the virus and its ultimate elimination depends on therapeutic care.Keywords: Corona virus, COVID-19, China, European countries, USA, Other Asian countries.